Elemental mercury reaction chemistry on brominated petroleum cokes. (November 2017) - Xiao, Yi; Pudasainee, Deepak; Gupta, Rajender; Xu, Zhenghe; Diao, Yongfa
Abstract: Activated carbon injection is a proven technology to capture mercury from flue gases. Due to the high cost and environmental concerns related to its disposal, high efficiency and low-cost sorbents have been studied to replace activated carbon. In this study, the petroleum coke obtained from two Canadian petroleum refineries, with high inherent sulfur content and impregnated with bromine, was compared to investigate elemental mercury capture mechanisms. These carbon-based sorbents showed excellent mercury removal efficiency at 100 and 200 °C. Elemental analysis, Brunauer–Emmett–Teller surface area, pore volume and thermogravimetric analysis were used to characterize the sorbents. X-ray photoelectron spectroscopy was used to examine the significant changes in chemistry and oxidation states of Br, S and Hg on the sorbent surface. More active mercury binding sites were created on brominated petroleum cokes after the chemical-mechanical bromination process. The inherent thiophene and organic sulfide in petroleum coke played a dominant role in mercury capture. Graphical abstract: